Alterations of glucocorticoid receptor gene methylation in externalizing disorders during childhood and adolescence - Heinrich, Angela; Brandeis, Daniel; Schmidt, Martin H.; Banaschewski, Tobias; Laucht, Manfred; Rietschel, Marcella (Behavior genetics, 2015)
Epigenetic modulations are a hypothesized link between environmental factors and the development of psychiatric disorders. Research has suggested that patients with depression or bipolar disorder exhibit higher methylation levels in the glucocorticoid receptor gene NR3C1. We aimed to investigate whether NR3C1 methylation changes are similarly associated with externalizing disorders such as aggressive behavior and conduct disorder. NR3C1 exon 1F methylation was analyzed in young adults with a lifetime diagnosis of an externalizing disorder (N = 68) or a depressive disorder (N = 27) and healthy controls (N = 124) from the Mannheim Study of Children at Risk. The externalizing disorders group had significantly lower NR3C1 methylation levels than the lifetime depressive disorder group (p = 0.009) and healthy controls (p = 0.001) This report of lower methylation levels in NR3C1 in externalizing disorders may indicate a mechanism through which the differential development of externalizing disorders as opposed to depressive disorders might occur.